AB0100 PHENOTYPIC AND FUNCTIONAL CHARACTERIZATION OF SYNOVIAL FLUID-DERIVED FIBROBLAST-LIKE SYNOVIOCYTES IN RHEUMATOID ARTHRITIS. (2nd June 2020) - Køster, D.; Egedal, J. H.; Hvid, M.; Jakobsen, M. R.; Müller-Ladner, U.; Deleuran, B.; Kragstrup, T. W.; Neumann, E.; Nielsen, M. A.
Abstract : Background: Fibroblast-like synoviocytes (FLS) are central cellular components in persistent inflammatory joint diseases such as rheumatoid arthritis (RA). Pathological subsets of FLS have been identified from synovial tissue. However, the synovial tissue obtained from arthroplasty procedures is acquired at late disease stages and the cellular yield obtained from synovial tissue biopsies is fairly low. Collectively, challenging the robustness of human RA in vivo and in vitro models. FLS obtained from the synovial fluid (SF-FLS) are proposed as an alternative source of FLS, but a detailed phenotypical and functional characterization of FLS subsets from the synovial fluid has not been performed. Objectives: The aim of this study was to determine the phenotypical and functional characteristics of synovial fluid-derived fibroblast-like synoviocytes in rheumatoid arthritis. Methods: In the present study, paired peripheral blood mononuclear cells (PBMC) and SF-FLS from patients with RA were obtained (n=7). FLS were isolated from the synovial fluid by a strict trypsinization protocol 1 and their cellular characteristics and functionality were evaluated at passage 4. Monocultures (SF-FLS) and autologous co-cultures (SF-FLS and PBMC) were established from five patients with RA and subsequently evaluated by flow cytometry, Western blotting and multiplex immunoassays. Human cartilage-sponges (n=3) with SF-FLS and without SF-FLS (n=3) were co-implanted subcutaneously in SCID mice (n=15), mice with only cell-free human cartilage-sponges were used as controls (n=12). After 45 days, the implants were evaluated using stained sections to determine the SF-FLS invasion score based on perichondrocytic cartilage degradation. Data are expressed as median (25-75 percentile). P-values <0.05 were considered statistically significant. Results: The homogeneous subpopulations of FLS, isolated from the synovial fluid, were negative for CD34 and CD45 [98.9%, (97.5-99.7]) and positive for Thy-1 and PDPN [94.6%, (79.9-97.4]). Without stimulation, RA SF-FLS showed high and comparable levels of NFκB related pathway proteins and secreted multiple pro-inflammatory cytokines and chemokines dominated by IL-6 [2648 pg/mL, (1327-6116)] and MCP-1 [2458 pg/mL, (692-8719)]. SF-FLS increased their ICAM-1 and HLA-DR expression after encountering autologous PBMCs (p<0.01), (p<0.05). Further, SF-FLS and PBMC interacted synergistically in a co-culture model of RA and significantly increasing the secretion of several cytokines (IL-1β, IL-2, IL-6, (p<0.01)) and a chemokine (MCP-1, (p<0.01)). The invasion score of the human SF-FLS in vivo was at primary site, [1.6, (1.3-1.7)] and contralateral implantation site [1.5, (1.1-2.2)]. The invasion score of the human SF-FLS-containing implants both at primary and contralateral site were significantly higher compared with cartilage-sponges evaluated from SF-FLS-free control mice (p<0001). Conclusion: This phenotypical and functional characterization of SF-FLS, acquired and activated at the site of pathology, lays a foundation for establishing in vivo and in vitro FLS models. These FLS models will be beneficial in our understanding of the role of this cellular subset in arthritis and for characterization of drugs specifically targeting this pathological RA FLS subset. References: [1]Nielsen M. A. et al. Responses to Cytokine Inhibitors Associated with Cellular Composition in Models of Immune-Mediated Inflammatory Arthritis. ACR Open Rheumatology, 2(1):3-10. http://doi.org/10.1002/acr2.11094 Disclosure of Interests: Ditte Køster: None declared, Johanne Hovgaard Egedal: None declared, Malene Hvid: None declared, Martin Roelsgaard Jakobsen: None declared, Ulf Müller-Ladner Speakers bureau: Biogen, Bent Deleuran: None declared, Tue Wenzel Kragstrup Shareholder of: iBio Tech ApS, Consultant of: Bristol-Myers Squibb, Speakers bureau: TWK has engaged in educational activities talking about immunology in rheumatic diseases receiving speaking fees from Pfizer, Bristol-Myers Squibb, Eli Lilly, Novartis, and UCB., Elena Neumann: None declared, Morten Aagaard Nielsen: None declared